Extrusion cooking increases soluble dietary fibre of lupin seed coat - Zhong, L.; Fang, Zhongxiang; Wahlqvist, M.; Hodgson, J.; Johnson, Stuart (Elsevier, 2019)
Extrusion cooking is widely used to improve the functional properties of dietary fibre of food processing by-products. This study investigated the capacity of extrusion cooking to increase the proportion of dietary fibre in the Australian sweet lupin seed coat which is soluble and modify its physicochemical properties (water binding capacity and water solubility). Fractional factorial design was used to identify which of the extrusion cooking factors most affected seed coat dietary fibre composition and physicochemical properties. Extrusion cooking significantly increased soluble dietary fibre content of lupin seed coat, from 29.03 g/kg dry basis to a maximum of 90.28 g/kg dry basis, while decreasing insoluble dietary fibre content from 898.91 g/kg dry basis to 828.85 g/kg dry basis. Water solubility increased (4.02–4.47% vs. 5.37–9.64% dry basis) whereas water binding capacity slightly decreased (3.84–3.88 g/g vs. 3.15–3.73 g/g dry basis) after extrusion cooking. The screw speed, total moisture content in barrel and barrel temperature were identified as the most important processing factors. These findings suggest that extrusion cooking could be a practical technology to increase the soluble dietary fibre content in lupin seed coat and enhance health benefits of the seed coat.